Mechanical behavior and surface properties of direct resin composites and resin-based CAD-CAM blocks - Fernandes Neto, Constantino (2025)
The focus of the investigations of this thesis was to evaluate mechanical properties and surface characteristics of resin composites exposed to modeling liquids (ML) and acid challenge analogue to dental erosion. Article 1 aims to evaluate the FS and surface properties of resin composites placed with the use of ML. The study methodology accounts with 3 resin composites Nanofilled - NF, Nanohybrid - NH, and Suprananomeric - SN, in shade A1E, which were handled with 3 methods MLK application: control - without ML (C), wetting resin - Ultradent (WR), modeling resin - Bisco (MR). Thirty bar-shaped (2x2x8 mm) and 10 disk-shaped (ø 10x1.5 mm) samples were made (n=40): 1-NF/C, 2-NF/WR, 3-NF/MR, 4-NH/C, 5-NH/WR, 6-NH/MR, 7-SN/C, 8-SN/WR, 9-SN/MR. FS (FS), Vicker\'s microhardness (VHN), surface roughness (Sa), and color stability (ΔEoo) were assessed. Except for FS, all the other properties were assessed at baseline and after aging with 14,600 brushing cycles and storage in cola drink for 7 days. Two-way ANOVA/Tukey tests were applied for FS and ΔEoo, and Twoway ANOVA repeated measures/Tukey for Sa and VHN at a 5% significance level. The results of FS showed significant differences for the material (p<0.01) and ML (p<0.01), being NF>NH>SN and WR~MR>C. VHN and Sa presented a significant effect of interaction for resin composite/ML (independent variables) and aging (dependent variable). VHN was reduced at baseline for NF/WR, NF/MR, and SN/MR. After aging, WR and MR groups presented lower VHN in comparison to the control groups. Increased Sa was seen for NF/WR, NF/MR, and NH/WR after aging. Color stability of NH and SN were affected by the presence of ML, being Delta-Eoo of NH/WR and SN/WR greater than 3. Regarding article 2, FS and surface characteristics of resin composites and CAD/CAM blocks were evaluated after erosive and abrasive challenge. For that, 120 resin composite disk specimens (ø14 mmx1.2 mm) were prepared and divided into 10 groups: Empress Direct (ED)-with erosive challenge (e), ED-control (c), Harmonize (HK)-e, HK-c, Camouflage Now (CN)-e, CN-c, Shofu Block (SB)-e, SB-c, Vita Enamic (VE)-e, VE-c. Specimens with erosive challenge were submitted to 5% hydrochloric acid (HCl, pH =1.2) flow for 96 h, and, subsequently, brushed for 14,600 cycles. FS, Sa, and VHN were performed. ANOVA-2-way/Tukey tests were applied and a significance level of 5% was applied. The results of FS have presented a significant difference for material variable (p>0.01) only, being CN and SB similar to each other and greater than HK, ED, and VE. Roughness was increased for all materials after erosive challenge and brushing, being VE the groups with smoothest surface. Microhardness was reduced for all materials submitted to HCl and toothbrushing. Greater differences were observed comparing different materials, being VE the highest hardness while ED and SB were the lowest. In conclusion, MLs resulted in improved FS, while compromising the surface properties. The erosive challenge with HCl acid flow has affected the surface of all resin composites tested without compromising the material FS.